Evaluation of percentage-based radon testing requirements for federally funded multi-family housing projects. Issue 4 (3rd April 2019) - Neri, Antonio
Abstract: Radon is a leading cause of lung cancer. Recommendations for radon testing in multi-family housing focus on testing a percentage of all units. There is considerable variability among recommendations as well as their implementation. I used the hypergeometric distribution to determine the probability of identifying one or more units with radon at or above 4.0 pCi/L for two prevalences (1:15, the U.S. average) and 1:3 (for states with many homes with radon ≥4.0 pCi/L) using two approaches. First, the distribution was used to evaluate the probability of finding one or more units with radon at or above 4.0 pCi/L when: (1) testing 10% or 25% of a range of ground-floor units; or (2) testing a varying percentage of units in 10-, 20-, or 30- ground-floor unit buildings. Second, the method was used to determine the number of units to be tested to identify one or more units with radon at or above 4.0 pCi/L with 95% probability, given a range of total ground-floor units. Analyses identified that testing 10% or 25% of ground-floor units had low probability of identifying at least one unit with radon at or above 4.0 pCi/L, especially at low prevalence. At low prevalence (1:15), at least 10 units need to be tested in structures with 20 or fewer total units; at high prevalence (1:3), at least 5 units need to be tested in units with structures having 10 or fewer units to achieve 95% probability of identifying at least one unit with radon at or above 4.0 pCi/L. These findings indicate that recommendations for radon testing in multi-family housing may be improved by applying a well-established and more rigorous statistical approach than percentage-based testing to more accurately characterize exposure to radon in multi-family housing units, which could improve lung cancer prevention efforts.